Regional Integration in the Great Lakes Region : comparative analysis Rwanda/Burundi - (:unkn) unknown (My University, 2016)
The history of regional integration in the Great Lakes is recent. To see Burundi and Rwanda truly enter into this process you have to wait the colonization. The Belgian mandate turns the two territories to the heart of Africa. This period will influence the first institutional integration with the Economic Community of Great Lakes Countries. However, we should remain cautius, since it is primarily paper integration. It is similar to other memberships of the two countries in this period, which is proving to be inadequate with their commercial channels. Regional organizations are also ineffective to resolve the refugee issue. The years 1993 and 1994 are internal ruptures for Burundi and Rwanda. They also cause a regional reversal, with the disintegration of the African Great Lakes : these are the Congolese wars. At the same time, both countries are shifting towards East Africa, where the EAC finally allows them a real opening up. The integration of Rwanda, however, seems more effective than that of Burundi.
Keywords: African Research